RESIN TYPE INFLUENCE ON MOULDED PARTS FINAL DIMENSIONS - RADU, Sever-Adrian; LEORDEAN, Vasile Dănuț; BÂLC, Nicolae; NEMEȘ, Ovidiu (Studia Universitatis Babeș-Bolyai Chemia, 2015)
Silicone rubber moulding is a perfect solution to fill the gap between rapid prototyping and prototyping injection moulding. Silicone moulds reproduce the tiniest of details, so the quality of the pattern is critical; they are also a fast and affordable solution for functional prototypes and low volume production. A experimental method using vacuum casting of resin parts in flexible moulds is presented in this paper. During the experimental investigations technological features of casted material, volume of air traps, optimal working parameters and dimensional accuracy of the manufactured parts were studied. Based on these results, the corrective coefficients applicable to CAD dimensions to fabricate the master models by SLS were determined.